Talented teachers : the essential force for improving student achievement - Solmon, Lewis C.; Schiff, Tamara Wingard, 1963- (Milken Family Foundation series on education policy., 2004)
This book provides readers with the opportunity to hear what experts in the educational community think about the myriad issues involved in improving the quality of all teachers in our nation's classrooms.